Histomorphometric study of the follicles of the ovary in Bangladeshi women - Perven, Hosna Ara; Nurunnabi, Abu Sadat Mohammad; Ara, Shamim (Journal of Bangladesh Society of Physiologist, 2013)
Background: The accurate assessment of size and number of ovarian follicles are paramount to understanding the physiology of female reproduction. Objective: To observe the variation in size of the Graafian follicle and follicular number with age in Bangladeshi women. Methods: This descriptive type of study was done in the Department of Anatomy, Dhaka Medical College, Dhaka, from January to December 2009, on 140 post mortem human ovaries collected from 70 unclaimed female dead bodies from the morgue of Forensic Medicine, Dhaka Medical College, Dhaka. The samples were divided into three age-groups including group A (10-13 years), group B (14-45 years) and group C (46-52 years). 10 best prepared histological slides from 14-45 years age group were examined to determine the average size of Graafian follicle and 20 slides from each group were taken to determine the number of follicles. Results: The average diameter of the Graafian follicles of the right is slightly higher than that of the left ovary but not statistically significant (p>0.05). No difference was found in follicular number in between the right and the left ovaries at any age group. However, the difference in number of the follicles of the ovary were statistically significant in between age groups A & C and B & C (p<0.001). Conclusion: The average diameter of Graafian follicle was found greater in the right ovary than the left ovary. However, the number of ovarian follicles was found to decrease in old age. DOI: http://dx.doi.org/10.3329/jbsp.v7i2.14458 J Bangladesh Soc Physiol. 2012, December; 7(2): 89-93